Material Design for “Am I Doing It Right?’ Book as Identity Search Media for Young Designers in Modern Era - Christian, Calvin (VCD: Journal of Visual Communication Design, 2021)
The content making of the "Am I Doing It Right?" book as a medium for searching the identity of young designers in the modern era is an initiative of the writer to participate indirectly in the mental development and mindset of young designers in Indonesia. In this modern era, designers often get less favorable views from society, many feel that the role of a designer is trivial. Departing from this problem, the authors have researched literature reviews that discussed the history of the designer profession, the true purpose of it, the role they held in society, the view of the social community towards the profession of designer, and ways of addressing the profession as a designer. Literature reviews will be carried out on at least fifteen scientific papers and books that discuss topics related to designer identity in the world. Keywords: Identity, Designer, Role, Profession